IMPLEMENTASI AKUNTABILITAS DAN ETIKA PROFESI DALAM PENGELOLAAN SUMBER DAYA MANUSIA PADA ORGANISASI PUBLIK - Putra, Arta Rusidarma; Romli, Ombi; Komarudin, Mochamad Fahru; Suflani, Suflani; Afriani, Raden Irna (Bhinneka Multidisiplin Journal, 2025)
This study aims to analyze the implementation of accountability and professional ethics in human resource management within public organizations in Serang City. The research employs a descriptive qualitative approach using observation, in-depth interviews, and documentation techniques involving civil servants and structural officials. The results indicate that accountability in output and process has improved through digital reporting and merit-based systems, yet public participation in supervision remains limited. In terms of professional ethics, employees show strong moral commitment, though professionalism and digital competence need enhancement. The study concludes that successful implementation of accountability and professional ethics relies heavily on leadership, organizational culture, and civil servants’ commitment to upholding good governance principles.